The value preferences of the Anilaonon as shown in the thematic pattern of his programs. - Pasadilla, Lenny Rose
The study is entitled "The Preferences of the Anilaonon as shown in the thematic pattern of his folksongs.", The respondents consisted of 41 native residents living in 21 barangays that comprise the town of Anilao. Taped recording was used to gather 80 folksongs from the respondents. The researcher's self-designed information sheet was utilized to solicit the name of the barangay, the name of the folksongerand the title/s of the folksong/s. Each folksong was subjected to content analysis inorder to find out the thematic pattern distinctive of the Anilao folksongs. The values found in the folksongs were analysed using frequency count and percentage with references to the majority criterion. Value preferences were determined by a "present" and "absent" tabulated result such that a particular value was preferred if, basing on the "present" table, it obtained the score of one half plus one or 41 of the total number of folksongs which is 80. The 80 flksongs generally revealed 12 specific values namely: Trust, Word of Honor, Sincerity, Belief in Fate, Love of Parents, Sense of Hope, Appreciation of Nature, Remembering the Dead and Loyalty. Results showed that the value preferences of the Anilaonon were: Trust, Word of Honor, Sincerity, Love of Partner and Loyalty.